The Role of Javanese Architecture in Reflecting the Cultural Values, Spirituality, and Belief System of the Javanese People - Dea Syahnas Paradita; Henny Tri Hastuti Hasana; Indy Rafia; Yudi Wibowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Abstract. Traditional Javanese architecture, especially joglo houses, reflect the harmonious relationship between humans, nature, and God through designs that are loaded with symbolism and philosophy. The joglo house not only serves as a place to live, but also as a space for religious and social rituals, reflecting the spiritual values and belief system of the Javanese people. In this article, we discuss the elements of joglo house design, such as soko guru, towering roofs, and spatial layouts that depict social and spiritual hierarchies. This study uses a qualitative approach based on literature studies to analyze how traditional Javanese architectural design reflects the cultural values and spirituality of its people. The results of the study show that the preservation of joglo houses as a cultural heritage is very important, but it faces great challenges due to modernization and urbanization. Preservation efforts through cultural education, culture-based tourism, and cross-sectoral cooperation are relevant solutions to maintain the continuity of this traditional architecture.